(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to explore the impact of media legislation on freedom of expression in local journalism in Saudi Arabia by analyzing the relationship between the legal and regulatory frameworks governing media practices and their influence on journalists’ freedoms and editorial practices. The study adopted a content analysis methodology, reviewing relevant literature and previous studies, as well as examining media cases and legal reports issued by regulatory bodies. It explored the legislative framework governing local journalism, including regulations related to publishing, electronic journalism, and digital media. The findings reveal that Saudi media legislation strives to balance national security and societal values with promoting freedom of expression and reinforcing the watchdog role of the press. However, the study identified challenges faced by journalists and media institutions, including restrictions on media content, licensing mechanisms, and legal accountability. The study recommends revising and updating media legislation to enhance transparency and provide a broader space for expressing opinions in alignment with international human rights standards and freedom of the press. It also emphasizes the importance of raising legal awareness among journalists and offering training programs to avoid legal violations. Additionally, the study calls for involving civil society in shaping media policies to foster a more flexible and effective media environment.